Modeling of snow cover on glaciers of the Caucasus and Kamchatka Peninsula - I. M. Sushintsev; E. D. Drozdov; P. A. Toropov; V. N. Mikhalenko; M. A. Vorobiev; A. G. Hayredinova (Лëд и снег, 2025)
The paper evaluates the possibility of using a computing complex that includes a SNOWPACK model and an algorithm for calculating orographic precipitation addition to reproduce snow cover in mountainous areas. This model complex was tested in the conditions of two contrasting mountain-glacial systems provided with in-situ data: the Central Caucasus (using the example of Mount Elbrus), and Kamchatka(using the example of the Ushkovsky volcano). Numerical experiments were carried out for the period of 09. 2023–02. 2024 for Elbrus and for the period of 1986–1997 for Ushkovsky, ERA5 reanalysis data wasused as a forcing. It is shown that on a seasonal scale for the Elbrus volcano, the simulation results are in good agreement with the field data: the error in the amount of snow accumulation was 3 cm, for the temperature inside the whole snow column mean average error was 1.4 °C with a coefficient of determination R2= 0.96. For Ushkovsky, 3 numerical experiments were conducted with different input data on precipitation. The simulation results were compared with the data from the 1996 ice core. When using the orographic precipitation model, the error in reproducing accumulation over 10 years was reduced to 25 % compared to 40 % according to the ERA5 reanalysis. At the same time, the model described the stratigraphy of the snow cover well: 4 out of 5 ice formations were reproduced. It is shown that the presented model tool can be used to approximate the dynamics of snow accumulation on long time scales and to analyze changes in ice formation conditions on mountain glaciers. Possible ways of the model complex developing are also discussed, which will allow more accurate assessment of snow column structure and reproduction of ice formations. According to the drilling data of 2022, it was revealed that the density profile of the Ushkovsky volcano is very different from that presented in the 1996 study. Previously, only about 4 % of ice was observed in the snow-firn stratum, currently its content has increased to 53% of the entire profile. Thus, climate change has affected the snow cover structure of Kamchatka’s high-altitude glaciers. This is manifested in an increase in the frequency of positive summer temperatures over the past decades, which leads to melting and infiltration of liquid moisture into the snow-firn stratum.